The Influence of Teachers' Emotional Skills and the Application of Pedagogical Skills on Teachers' Teaching Competence - Irawati, Novita (Proceedings Series of Educational Studies, 2025)
This article explores the impact of teachers' emotional skills and the application of pedagogical skills on their teaching competence. This study aims to determine the extent to which both factors contribute to teachers' basic teaching abilities. The method used is a survey with quantitative analysis, involving a number of teachers from various educational institutions. The results of the study indicate that emotional skills contribute significantly to teacher competence, with an influence of 9%, while the application of pedagogical skills contributes 6%. Overall, both factors contribute 14% to teaching ability, while the rest is influenced by other factors. These findings emphasize the importance of developing emotional skills, such as empathetic communication and sensitivity to student characteristics, as well as the application of effective pedagogical strategies. This study recommends that teacher training programs focus on improving emotional and pedagogical skills to optimize teaching competence